New developments in angiography for the diagnosis and management of diabetic retinopathy. (September 2020) - Mustafi, Debarshi; Saraf, Steven S.; Shang, Qing; Olmos de Koo, Lisa C.
Abstract: The most common microvascular complication of diabetes is diabetic retinopathy, the leading cause of blindness in adults of working age. Our understanding of the vascular changes in diabetic retinopathy was enhanced by the demonstration of fluorescein angiography (FA) in the human retina for the first time in 1961. It was subsequently integrated with digital fundoscopic imaging to become an invaluable technique in evaluation of the retinal vasculature. The recent development of OCT-angiography (OCT-A) has revolutionized the clinician's ability to examine the retinal vasculature without the need for injection of a contrast dye. By coupling OCT, which can provide noninvasive cross-sectional imaging of the central retina, with angiography in OCT-A, one can reveal retinal perfusion by allowing visualization of the depth-resolved retinal capillary plexus. OCT-A has allowed for more precise delineation of changes in the retinal microvasculature, specifically the alterations of retinal vasculature and loss of capillary perfusion from chronic microvascular occlusion in diabetic retinopathy.